"They are human beings, they are Swazi": intersecting stigmas and the positive health, dignity and prevention needs of HIV‐positive men who have sex with men in Swaziland. Issue 4 (2nd December 2013) - Kennedy, Caitlin E; Baral, Stefan D; Fielding‐Miller, Rebecca; Adams, Darrin; Dludlu, Phumlile; Sithole, Bheki; Fonner, Virginia A; Mnisi, Zandile; Kerrigan, Deanna
Abstract : Introduction: Despite the knowledge that men who have sex with men (MSM) are more likely to be infected with HIV across settings, there has been little investigation of the experiences of MSM who are living with HIV in sub‐Saharan Africa. Using the framework of positive health, dignity and prevention, we explored the experiences and HIV prevention, care and treatment needs of MSM who are living with HIV in Swaziland. Methods: We conducted 40 in‐depth interviews with 20 HIV‐positive MSM, 16 interviews with key informants and three focus groups with MSM community members. Qualitative analysis was iterative and included debriefing sessions with a study staff, a stakeholders' workshop and coding for key themes using Atlas.ti. Results: The predominant theme was the significant and multiple forms of stigma and discrimination faced by MSM living with HIV in this setting due to both their sexual identity and HIV status. Dual stigma led to selective disclosure or lack of disclosure of both identities, and consequently a lack of social support for care‐seeking and medication adherence. Perceived and experienced stigma from healthcare settings, particularly around sexual identity, also led to delayed care‐seeking, travel to more distant clinics and missed opportunities for appropriate services. Participants described experiences of violence and lack of police protection as well as mental health challenges. Key informants, however, reflected on their duty to provide non‐discriminatory services to all Swazis regardless of personal beliefs. Conclusions: Intersectionality provides a framework for understanding the experiences of dual stigma and discrimination faced by MSM living with HIV in Swaziland and highlights how programmes and policies should consider the specific needs of this population when designing HIV prevention, care and treatment services. In Swaziland, the health sector should consider providing specialized training for healthcare providers, distributing condoms and lubricants and engaging MSM as peer outreach workers or expert clients. Interventions to reduce stigma, discrimination and violence against MSM and people living with HIV are also needed for both healthcare workers and the general population. Finally, research on experiences and needs of MSM living with HIV globally can help inform comprehensive HIV services for this population.